Passive resistance : portuguese diplomacy of contraband trade during king John V's reign, 1706-1750 - Pijning, Ernst (1997)
During the reign of king John V foreign diplomats negotiated their nation's ability to engage in illegal practices in Portugal and her colonies. In return for their military support and protection, English, French and Dutch representatives pressed the Portuguese government to condone their nation's involvement in contraband trade. The ability of the Portuguese government to hold off such foreign pretensions, depended primarily on their room to manoeuver within European political theathers. [...]